INCREASING MOTIVATION TO LEARN ISLAMIC RELIGIOUS EDUCATION POST-EARTHQUAKE THROUGH REWARDS AND PUNISHMENTS - Gusnarib, Gusnarib; Askar, Askar; Ali, Ali (State Islamic University of Datokarama Palu, 2022)
The results of this study show that there are many ways that teachers can motivate students to learn at SMK Negeri 1 Palu after the earthquake, among others, by using various methods and activities. Because when the teacher uses the same method continuously it can cause boredom and reduce the enthusiasm for learning of students. Furthermore, the teacher can also increase the learning motivation of students by making students active. After the earthquake the teacher gave more prizes to students who had high scores in Islamic Religious Education subjects such as tuition free scholarships for 6 months and usually the teacher gave praise that made students more motivated in learning. After the earthquake, students who violate the subject of Islamic religious education will be given educational punishments, namely two different punishments depending on the size or size of the mistakes made by students. The background of the formation of rewards and punishments at SMK Negeri 1 Palu is the desire to reward students who are active / accomplished and if they provide sanctions / penalties based on objective data.